Accuracy of a history of blood donation from surrogate witnesses: data from the UK TMER study. Issue 5 (15th May 2018) - Mackenzie, J. M.; Turner, M.; Morris, K.; Field, S.; Molesworth, A.M.; Pal, S.; Will, R. G.; Llewelyn, C. A.; Hewitt, P. E.
Abstract : Look‐back studies of blood transfusion in Creutzfeldt–Jakob disease commonly rely on reported history from surrogate witnesses. Data from the UK Transfusion Medicine Epidemiology Review have been analysed to determine the accuracy of the blood donation history provided by the relatives of cases. Our results show that only a small percentage of cases were found to be registered as donors on UK Blood Service (UKBS) databases when there was no family report of blood donation. In contrast, a history of reported donation was less accurate.